Efektivitas Intervensi Pencegahan Diabetes Mellitus Berbasis Komunitas di Desa Baru - Eliska, Eliska; Junaisa Intan Farashati; Sheila Megarani; Azzahra Chandra Syafira; Ainun Nuraida; Luthfiah Alisa (Yayasan Jompa Research and Development, 2025)
Diabetes Mellitus (DM) is a non-communicable disease with a high prevalence in Indonesia and is a public health problem that requires continuous prevention efforts. This study aims to describe the effectiveness of community-based interventions in increasing public knowledge and awareness regarding DM prevention. The research design used was descriptive with a community-based participatory approach. The study population included the community in the Field Learning Experience (PBL) activity area of ​​students of the Faculty of Public Health, UIN North Sumatra in July–August 2025. The sample consisted of 525 participants divided into several target groups, including the elderly, elementary and junior high school students, women in religious schools, and DM sufferers. The sampling technique was purposive according to the activity targets. The research variables included increasing knowledge and awareness regarding DM prevention. Data were collected through observation, short questionnaires, and recording of activity results, then analyzed descriptively and presented as a percentage. The results showed that the success rate of the intervention varied between 70–90%, with the highest achievement in low-sugar snack education (90%) and the lowest in leaflet distribution (70%). The conclusion shows that community-based promotive and preventive interventions are effective in increasing health literacy and public awareness regarding DM prevention.